Homo psyche: on queer theory and erotophobia - Ashtor, Gila (Fordham University Press, 2021)
Frontmatter -- Contents -- Introduction: Homo Psyche: On Queer Theory and Erotophobia -- 1 What "Theory" Knew: Sedgwick, Queerness, Hermeneutics -- 2 The Genealogy of Sex: Bersani, Laplanche, and Self- Shattering Sexuality -- 3 Boundaries Are for Sissies: Violation in Jane Gallop and Henry James -- 4 Adults Only: Lee Edelman's No Future and the Limits of Queer Critique -- 5 Psychology as Ideology-Lite: Butler, and the Trouble with Gender Theory -- 6 Two Girls2: Sedgwick + Berlant, Relational and Queer -- Acknowledgments -- Notes -- Works Cited -- Index